Youth Justice and Migration Discursive Harms - Petintseva, Olga (Springer International Publishing, 2018)
This book examines the implications of the professional and judicial discourses on migrant youth in the Belgian youth justice system. Drawing on a detailed study of 55 court case files and in-depth interviews with over forty youth justice professionals, the book explores the problematisations of migrant Roma and Caucasian young people in the youth justice system to argue that they result in 'discursive harms'. It discusses the assumptions and the effects of explanations of deviant behaviour, ambiguities in representations of young people's agency and responsibility, differing assumptions about the moral potential of Roma and Caucasian families, and the reframing of assessments in school-based reports as signals of delinquency. The book reflects on how to address the 'discursive harms' identified and calls for a review of protection practices and ideals from a fundamental rights perspective. This book contributes to a topic that will have increasing significance for youth justice practice in Belgium as well as the rest of Europe.